2011
DOI: 10.1177/0143034311415906
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the whole-school approach to bullying: Really looking at the whole school

Abstract: The whole-school approach to bullying prevention is predicated on the assumption that bullying is a systemic problem, and, by implication, that intervention must be directed at the entire school context rather than just at individual bullies and victims. Unfortunately, recent meta-analyses that have looked at various bullying programs from many countries have revealed that whole-school interventions designed to combat bullying have had limited success in reducing bullying. The purpose of the present study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
122
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(145 citation statements)
references
References 62 publications
11
122
2
10
Order By: Relevance
“…Our thesis draws from three theoretical perspectives. First, consistent with other authors concerned with the nature of bullying (Swearer et al 2010;Richard, Schneider, andMallet 2012), Bronfenbrenner's (2005) bio-ecosystemic theory of human development provides a broad framework through which bullying is understood to be influenced by the interaction between the individual and the microsystems he/she inhabits (e.g. peer group, school, home, community)., Lewis and Norwich's (2005) 'general differences' model for understanding special educational needs and disabilities (SEND) informs the positioning of our work.…”
Section: What Is Bullying?supporting
confidence: 60%
See 2 more Smart Citations
“…Our thesis draws from three theoretical perspectives. First, consistent with other authors concerned with the nature of bullying (Swearer et al 2010;Richard, Schneider, andMallet 2012), Bronfenbrenner's (2005) bio-ecosystemic theory of human development provides a broad framework through which bullying is understood to be influenced by the interaction between the individual and the microsystems he/she inhabits (e.g. peer group, school, home, community)., Lewis and Norwich's (2005) 'general differences' model for understanding special educational needs and disabilities (SEND) informs the positioning of our work.…”
Section: What Is Bullying?supporting
confidence: 60%
“…This view is supported by the research of Robertson, Chamberlain, and Kasari (2003), who found that the quality of teacher-student interactions influenced relationships, which in turn had a bearing on peer acceptance for students with ASC. The importance of relationships can also be seen in the general bullying literature, where evidence suggests there are fewer incidents in schools with more positive teacher-student relations (Raskauskas 2010;Richard, Schneider, and Mallet 2012). Sciutto et al (2012) identified a number of key teacher qualities that were perceived to have a positive impact in this regard, including tolerance, acceptance, and encouragement of differences and individuality (rather than conformity), overcoming impressions and recognising that 'the usual' will not work (in terms of pedagogic approaches), showing empathy, respect, and liking for students with ASC, and taking the time to understand individual needs.…”
Section: Teaching and Support Staffmentioning
confidence: 98%
See 1 more Smart Citation
“…Recommended are multicomponent schoolwide programs based on the SocialEcological Diathesis-Stress Model, 17 which emphasizes the dynamic and fluid nature of bullying across the individual, family, peer group, school and community contexts. [30][31][32] For instance, the Cyber Friendly Schools Program 33,34 is an online whole-school cyberbullying prevention and intervention program built on a social-ecological approach; it reported a significant decline in CV perpetration at one year in a group randomized controlled trial. 35 From a legal perspective, in Canada, cyberbullying can be addressed under civil law or criminal law.…”
Section: Cyberbullying and Health Outcomesmentioning
confidence: 99%
“…Specific to the findings around attachment, the causal direction of this relationship cannot be established through our results, unfortunately. Some studies suggest that students who are frequently victimized feel a lower sense of belonging (Eisenberg et al 2009), while other studies reported less bullying at schools where students report higher school attachment (Hong and Espelage 2012;Richard et al 2012), suggesting that decreases in victimization are associated with better school attachment. Nonetheless, the consistency of this finding indicates that school attachment is important and that further research in this area is justified.…”
Section: Discussionmentioning
confidence: 99%